ANALYSIS OF THE ACTIVITIES OF TOURISM SECTOR BUSINESS ENTITIES IN UKRAINE - KOVAL, Vitaly; NESTORISHEN, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The development of entrepreneurship in the tourism sector is a crucial vector for the economic recovery of Ukraine's national economy and territorial communities, which in turn requires an in-depth analysis of the economic environment in which they operate. Furthermore, the high relevance of studying the activities of tourism business entities is also due to the dynamic changes in the economic environment, caused by both internal transformations and external factors, including military actions, global crises, and shifting consumer priorities. Particular attention needs to be paid to the analysis of enterprises' economic resilience to crises and their ability to adapt, taking into account the transformation of demand for tourism services. The results of such an analysis can serve as a basis for developing recommendations to support and stimulate entrepreneurial activity in the tourism sector, thereby contributing to its recovery and sustainable growth in the face of modern challenges.The aim of the research is to analyze the activities of tourism business entities in Ukraine, in the context of identifying the main trends, problems, and prospects for development in the face of contemporary challenges.Since the beginning of 2020, under the influence of globalization processes in the global tourism services market, significant transformations have been taking place in the domestic tourism market as well. In particular, during this period, tourism and hospitality industry enterprises faced unprecedented negative impacts caused by the global COVID-19 pandemic for the first time. This led to the introduction of national-level restrictions, which significantly narrowed the possibilities for movement both within and between countries. An analysis of the economic indicators of the tourism industry for 2024 demonstrates both positive and concerning trends. The overall volume of tax revenues has significantly increased, reaching 2938 million UAH, which is 43% more than in 2023 and 32% more compared to 2021. This increase indicates a gradual recovery and growth of the industry, despite challenging external circumstances.It should be noted that the domestic tourism industry has significant development prospects, which depend on several key factors. Firstly, the stabilization of the military and political situation, which will allow for the restoration of infrastructure and the attraction of foreign tourists. Secondly, tourist safety, which requires the implementation of modern technologies and service certification. Thirdly, the digital transformation of the industry, which will improve service quality and expand access to tourism services. Fourthly, the development of niche tourism types, such as ecotourism, gastronomic tourism, and cultural-historical tourism, which will allow for the creation of unique tourism products.
Keywords: analysis; business entities; tourism sector; taxes